Pengaruh Suplementasi Besi dan Vitamin C terhadap Asupan Zat Gizi dan Kadar Haemoglobin Anak Sekolah Dasar di Kabupaten Kapuas, Kalimantan Tengah - Wiwik Suharti, Hamam Hadi (Berita Kedokteran Masyarakat (BKM), 2003)
Background: Anemia prevalence among Indonesian school children is still high amount-ing to 57%. Iron deficiency has been reported to be associated with anemia and poor growth of children. Whether iron supplementation can improve nutrient intakes and haemoglobin level of school children remains unclear.Objective: This study was conducted to find out whether iron supplementation with vitamin C increases nutrient intakes and haemoglobin level of elementary school chil-dren with poor nutritional status.Methods: This was a randomized, double blind, placebo controlled trial conducted in Kapuas regency, Central Kalimantan. Subjects of this study were elementary school children aged 8-12 years with Weight for Height Z Scores